EMPOWERING STRATEGIES OF SMES IN WEST AFRICA BY THE ISLAMIC DEVELOPMENT BANK FOR SUSTAINABLE DEVELOPMENT AND POVERTY REDUCTION - Sackor, Muhammed (PT. Antis International Publisher, 2025)
Objective: This study examines the challenges and competitiveness of small and medium-sized enterprises (SMEs) in West Africa, focusing on the funding support provided by the Islamic Development Bank (IsDB) to address critical socio-economic issues such as poverty and unemployment in the region. Method: The research utilizes empirical evidence from previous studies conducted by the World Bank and other multilateral institutions, analyzing key obstacles to the successful implementation and sustainability of SMEs in West African countries. Results: The findings reveal significant challenges that hinder the growth and sustainability of SMEs in the region, including limited access to financing, inadequate infrastructure, and regulatory barriers. However, the support provided by IsDB plays a crucial role in overcoming some of these challenges, promoting the success of SMEs in the region. Novelty: This study contributes new insights into the role of the IsDB in supporting SME growth in West Africa, offering practical recommendations to enhance the success and prosperity of SMEs in the region. The paper emphasizes the importance of addressing structural barriers to ensure the long-term sustainability of SMEs in the context of West Africa's socio-economic challenges.